Delhi Jal Board : Wastewater Management PPP Options Study - World Bank (Washington, DC, 2013)
Delhi Jal Board (DJB) is exploring options for public private partnerships (PPP) in the wastewater services as part of a strategy to expand sewerage access and to meet its environmental obligations. The purpose of this report is to identify those models of partnership which are most relevant to DJB's situation and to discuss some of the advantages and risks associated with them. The report goes on to propose an outline for a possible PPP strategy. Finally, PPPs have to be paid for, like any other investment. A good financial model to understand the sources of financing (both capital and operational) is therefore a fundamental part of preparing a PPP program. This will demonstrate the project's viability both to DJB and to the potential bidders.